Soil microbial diversity, functionality, and community structure are differently affected by diverse types of biochar - Dominchin, Maria Florencia; Barbero, Florencia Magalí; Verdenelli, Romina Aylén; Paolinelli, Marcos; Aoki, Antonio; Faggioli, Valeria Soledad; Meriles, José Manuel (Wiley, 2025)
Using organic wastes for biochar production represents an innovative approach to waste management, facilitating safe residue disposal while producing a soil amendment by-product. The characteristics of biochar strongly depend on the chemical composition of the feedstock utilised in its production. Consequently, even within the same agroecosystem, different types of biochar may produce varying effects on soil chemistry and biology. In a greenhouse experiment, we assessed the impact of poultry manure and peanut shell biochars on soil chemical properties and their effects on microbial community structure, abundance, diversity and functions analysed through biochemical and molecular approaches. Thus, a two-factor experimental design was established, considering biochar type (poultry manure and peanut shell biochars) and rate (0%, 1%, and 3% w/w). Our findings highlighted that the intrinsic properties of biochar significantly influenced its ability to induce changes in the analysed variables. Poultry manure biochar exhibited greater efficacy in increasing soil pH and EC, simultaneously enhancing fungal and total biomasses. Meanwhile, peanut shell biochar increased N content and decreased C/N, slightly impacting fungal and total biomasses. The effects of biochars on FAMEs and chemical variables were dose-dependent; the higher the application rate, the greater the observed effect. Interestingly, different biochar types affected distinct bacterial taxa abundances. Among the dominant Phyla, while poultry manure biochar increased the relative abundance of Chloroflexi and decreased that of Proteobacteria, peanut shell biochar increased Acidobacteria and reduced Firmicutes phyla. The biochar rate did not affect bacterial abundance. Notably, only peanut shell biochar increased bacterial richness. Poultry manure biochar positively impacted functions related to metabolism, whereas the effect of peanut shell biochar was less evident. Our study revealed that the intrinsic characteristics of biochar significantly modulate the structure and functionality of the soil microbial community. Therefore, understanding the inherent characteristics of biochar is crucial to promoting the development of specific groups of soil microorganisms, thus optimising the cycling of essential nutrients.